Pengaruh Likuiditas, Solvabilitas dan Profitabilitas terhadap Harga Saham di Bursa Efek Indonesiaa - Morina Tarigan Sibro; Agus Defri Yando (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2021)
The percentage rate of the client items area withinside the remaining five years has increased. The cause of this examine became to decide the impact of liquidity, solvency and profitability on inventory costs. The approach used on this studies is secondary records evaluation of the economic statements of businesses indexed at the Indonesia Stock Exchange from 2015-2019 with the aid of using figuring out non-chance purposive sampling the use of exclusion standards which will acquire 60 populations and 28 samples which will acquire a hundred and forty economic document records. The effects of the partial evaluation display that liquidity has no big impact on inventory costs with a tcount of 0.305 0.05, solvency has a big impact on inventory costs with a fee of tcount 2.398> t desk 1, 97756 and chance (Sig.) Of 0.018 <0> t desk 1.97756 and a chance (Sig.) Of 0.012 <0> 2.sixty seven from the F desk and a importance fee of 0.007